2015
DOI: 10.4028/www.scientific.net/amr.1117.235
|View full text |Cite
|
Sign up to set email alerts
|

Development of Textile Based Sewn Switches for Smart Textile

Abstract: The intelligent systems of smart textile should contain flexible electronics, for example, sewn or stitched textile elements that function as conductive traces, sensor elements, electrodes or switches. The experiments for development of sewn touch and push switches are performed. For this reason silver coated multifilament polyamide and multifilament stainless steel yarns were used and their properties and suitability tested. Tests include the changes of electrical resistance of yarns during tension, measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Sahta et al [ 102 ] developed textile-based sewn switches by using commercially available conductive thread based on silver-coated multifilament polyamide thread and often used to connect devices within e-textile structures. Silver-coated multifilament polyamide yarns are elastic, flexible, and with respect to their textile properties, correspond to the “conventional” textile yarns.…”
Section: Integration Techniquesmentioning
confidence: 99%
“…Sahta et al [ 102 ] developed textile-based sewn switches by using commercially available conductive thread based on silver-coated multifilament polyamide thread and often used to connect devices within e-textile structures. Silver-coated multifilament polyamide yarns are elastic, flexible, and with respect to their textile properties, correspond to the “conventional” textile yarns.…”
Section: Integration Techniquesmentioning
confidence: 99%
“…Šahta et al. [44] have studied the effect of interlinings on the electro-conductive systems used in smart garment. It is reported that interlining protects the system of wiring from moisture while washing.…”
Section: Interliningmentioning
confidence: 99%
“…E-textiles, that is, normal fabrics that integrate multifunctional electronics such as circuits [1], sensors [2][3][4], displays [5,6], switches [7], monitors [8], medical diagnostic components [9], have demonstrated great potential and are rapidly gaining wide attention owing to the enormous demand for wearable technologies in recent years [10,11]. However, with the recent progress in multifunctional e-textiles, application of conventional energy storage devices (batteries and supercapacitors) is not possible, considering the heavy-weight, lack of comfort, flexibility, and free maintenance, and the need for frequent charging [12].…”
Section: Introductionmentioning
confidence: 99%